Global, regional, and national burden of genitourinary cancers in 204 countries and territories, 1990–2021: a systematic analysis for the global burden of disease study 2021 - Zhiyong Zhang; Yingwei Xie; Lei Liu; Yongtao Wang; Shuang Li; Li Chen; Xiangbo Zeng; Yuanchao Zhu; Yishan Zhang; Yongyuan Xiao; Fengjin Zhao; Bihong Xu; et al. (Journal of the National Cancer Center)
Background: Genitourinary cancers constitute a significant portion of the global cancer burden and have emerged as a prominent cause of cancer-related mortality. However, there remains a paucity of up-to-date statistical analyses that meticulously examine the global and national shifts in the epidemiology of genitourinary cancers. Our study aimed to provide a comprehensive understanding of the global distribution and progression of genitourinary cancers through analyses of the recently updated 2021 Global Burden of Disease (GBD) database. Methods: This study presented the incidence, mortality, disability-adjusted life years (DALYs), and their respective age-standardized rates for four genitourinary cancers (bladder, kidney, prostate, and testicular cancers) by sex, age, and location from 1990 to 2021. Estimates for these data were presented with their 95% uncertainty intervals (UIs). Estimated annual percentage changes (EAPCs) and Bayesian Age-Period-Cohort (BAPC) models were utilized to further quantify the temporal dynamics of age-standardized rates (ASRs) in genitourinary cancers. Countries and territories were categorized according to socio-demographic index (SDI) quintiles. Results: Globally, with the exception of a sustained decline in age-standardized incidence rates (ASIRs) for bladder cancer (EAPC = −0.36%), the ASIRs for kidney, prostate, and testicular cancers demonstrated an upward trend from 1990 to 2021 (EAPC = 0.53%, 0.20%, and 1.43%, respectively). In terms of geographical regions, High-income North America had the highest ASIRs for both bladder (13.98 per 100,000 persons [95% UI, 12.96 to 14.61]) and prostate (47.02 per 100,000 persons [95% UI, 44.47 to 49.04]) cancers. Southern Latin America recorded the highest ASIRs for kidney (13.44 per 100,000 persons [95% UI, 12.27 to 14.73]) and testicular (4.98 per 100,000 persons [95% UI, 4.33 to 5.72]) cancers. Additionally, Central Europe (1.25% [95% CI, 1.12% to 1.38%]), East Asia (2.40% [95% CI, 2.21% to 2.59%]), Eastern Europe (3.74% [95% CI, 3.55% to 3.92%]), and the Caribbean (5.52% [95% CI, 4.32% to 6.74%]) exhibited the highest EAPCs for bladder, kidney, prostate, and testicular cancers, respectively. Unlike the ASIRs, age-standardized mortality rates (ASMRs) and age-standardized DALYs rates (ASDRs) showed a downward trend over time in all types of genitourinary cancers. The disease burdens of bladder, kidney, and prostate cancers were primarily distributed among older men, while testicular cancer mainly occurred in young men. Smoking remained the primary risk factor for bladder cancer. Meanwhile, high fasting plasma glucose and high body-mass index exerted increasingly significant impacts on bladder and kidney cancers, respectively, during the study period. Projections to 2050 suggest that the global burdens of genitourinary cancers are expected to decline to varying degrees. However, regional disparities in genitourinary cancer burdens are projected to persist. Conclusions: Although the results demonstrate a marginal decline in ASRs caused by genitourinary cancers, they still impose a considerable global burden and result in numerous deaths. Our study obtained and analyzed the latest epidemiological data of genitourinary cancers from the GBD 2021, offering valuable information for national healthcare professionals and policymakers to optimize resource allocation, manage costs more efficiently, and develop practical healthcare policies.